2004
DOI: 10.1074/jbc.m401182200
|View full text |Cite
|
Sign up to set email alerts
|

Two Exoribonucleases Act Sequentially to Process Mature 3′-Ends of atp9 mRNAs in Arabidopsis Mitochondria

Abstract: In plant mitochondria, transcription proceeds well beyond the region that will become mature 3 extremities of mRNAs, and the mechanisms of 3 maturation are largely unknown. Here, we show the involvement of two exoribonucleases, AtmtPNPase and AtmtRNaseII, in the 3 processing of atp9 mRNAs in Arabidopsis thaliana mitochondria. Down-regulation of AtmtPNPase results in the accumulation of pretranscripts of several times the size of mature atp9 mRNAs, indicating that 3 processing of these transcripts is performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
100
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 32 publications
5
100
0
3
Order By: Relevance
“…Therefore, hmtPAP is a key enzyme regulating both translation termination and mRNA metabolism in human mitochondria. In contrast, hPNPase acts degradatively, similar to E. coli or Arabidopsis organellar PNPases (6,37,49), and thus controls the extent of mitochondrial polyadenylation. However, it is also shown that hPNPase has in vitro PAP activity (Fig.…”
Section: Recombinant Hmtpap Has Polyadenylation Activity Inmentioning
confidence: 99%
“…Therefore, hmtPAP is a key enzyme regulating both translation termination and mRNA metabolism in human mitochondria. In contrast, hPNPase acts degradatively, similar to E. coli or Arabidopsis organellar PNPases (6,37,49), and thus controls the extent of mitochondrial polyadenylation. However, it is also shown that hPNPase has in vitro PAP activity (Fig.…”
Section: Recombinant Hmtpap Has Polyadenylation Activity Inmentioning
confidence: 99%
“…In plant mitochondria, PNPase, a 3′ to 5′ exoribonuclease, is involved in the generation of mature 3′ termini of transcripts such as atp9 mRNA but is also required for the removal of RNAs from the total mitochondrial transcript pool. 21,22 To check whether there is any connection between 5′ processing and the degradation of non-processed RNAs by PNPase, we established a transgenic Arabidopsis line expressing an artifical microRNA (amiRNA) targeting the corresponding mRNA (amiR-PNP-3, Fig. S6A).…”
Section: 34mentioning
confidence: 99%
“…Two enzymes were found to be involved in 3′ to 5′ exonucleolytic trimming of the mature 3′ ends. 21,22 The mitochondrial polynucleotide phosphorylase (PNPase) is capable to degrade large parts of the precursor transcript downstream of the mature 3′ terminus, whereas the fine-tuning of the 3′ termini is done by RNase R1 homolog (RNR1), which removes a few nucleotides left over by PNPase. Analogous to the plastid-type transcript processing, the P-class PPR protein MTSF1 binds to the 3′ terminal part of nad4 transcript and it is highly likely that this interaction impedes progression of the 3′ exonucleolytic activities and thus determines the mature 3′ end of this mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, two 3# to 5# exoribonucleases involved in the generation of 3# ends (RNR1 and PNPase) have been characterized by reverse-genetics approaches and, very recently, a similar approach identified a protein required for trans-splicing of nad1 transcripts in Arabidopsis (Arabidopsis thaliana) mitochondria (Perrin et al, 2004a(Perrin et al, , 2004bFalcon de Longevialle et al, 2007). Forward-genetics approaches have also been applied to identify genes for nuclear-encoded restorers of fertility in several cytoplasmic male sterility (CMS) systems.…”
mentioning
confidence: 99%
“…Detailed investigations of these posttranscriptional processes are still at the beginning and up to now have been predominantly descriptive. Although functional studies using in vitro or in organello systems have allowed some insight into the mechanisms of RNA editing, splicing, or 3# end formation Araya, 2001, 2002;Staudinger and Kempken, 2003;Takenaka and Brennicke, 2003;Perrin et al, 2004aPerrin et al, , 2004b, still very little is known about the trans-factors active in these processes. One of the least explored maturation steps is the generation of mature 5# ends of mitochondrial mRNAs.…”
mentioning
confidence: 99%